Central inhibitory mechanisms controlling water and sodium intake - Menani, José Vanderlei [UNESP]; De Luca, Laurival Antonio [UNESP]; de Paula, Patrícia Maria [UNESP]; de Andrade, Carina Aparecida Fabrício [UNESP]; de Oliveira, Lisandra Brandino [UNESP]; da Silva, Daniela Catelan Ferreira [UNESP] (My University, 2009)
Ingestion of sodium and/or water is controlled by excitatory mechanisms that involve stimuli like angiotensin II (ANG II), mineralocorticoids or hiperosmolarity acting on specific areas of the brain and by inhibitory mechanisms present in different central areas and involving different hormones and neurotransmitters that act to limit these behaviors. Recent studies have shown two important inhibitory mechanisms for the control of sodium and water intake: the inhibitory mechanism of the lateral parabrachial nucleus (LPBN) and the alpha2 adrenergic mechanism located in forebrain areas. In the LPBN different neurotransmitters like serotonin, cholecystokinin, glutamate, corticotropinreleasing factor, GABA and opioid may modulate the inhibitory mechanism. Interactions between neurotransmitters in the LPBN, like the interdependence and cooperactivity between serotonin and cholecystokinin have also been demonstrated. In the forebrain, mixed alpha2-adrenergic and imidazoline receptor agonists, like clonidine and moxonidine, are the most effective to inhibit water and sodium intake induced by different stimuli. Inhibition of water or NaCl intake dependent on alpha2-adrenergic receptor activation has been demonstrated with injection of these drugs into the lateral ventricle (LV), septal area, lateral preoptic area, and lateral hypothalamus. Previous and unpublished results presented in this chapter have shown that: A) in normovolemic rats, moxonidine injected into the LV induced c-fos expression in the organum vasculosum lamina terminalis (OVLT), ventral median preoptic nucleus (vMPN), paraventricular and supraoptic nucleus of the hypothalamus, while in sodium depleted rats, moxonidine reduced c-fos expression in the OVLT and increases it in the dorsal MPN; B) moxonidine bilaterally injected into basal amygdala (BA) reduced sodium depletion-induced sodium intake, while no effects were observed injecting moxonidine into the central amygdala; C) moxonidine into the LV reduced water and sodium intake and hypertension induced by daily subcutaneous (sc) injection of deoxycorticosterone; D) moxonidine injected into the LV also reduced food intake-induced water intake, but did not change food deprivation-induced food intake, suggesting that inhibitory effects of moxonidine in the forebrain are not due to non specific inhibition of behaviors; E) contrary to the inhibitory effects produced by injections into the amygdala, LV or other forebrain areas, bilateral injections of moxonidine into the LPBN increases sodium intake.
Keywords: Alpha2 -adrenoceptors; Lateral parabrachial nucleus; Moxonidine; Serotonin; Sodium appetite; Thirst